Factors determining the share price volatility: Evidence from listed companies in Sri Lanka - Lingesiya Kengatharan; Jeyan Suganya Dimon Ford (Universitas Trisakti, 2019)
The objective of this study is to investigate the factors determining the share price volatility of listed companies in Colombo Stock Exchange (CSE), Sri Lanka. A sample of 72 listed non -financial firms from CSE in Sri Lanka is examined using panel data analysis for a five years period from 2013 to 2017. Dividend payout ratio, dividend yield, dividend per share, sales growth, leverage, exchange rate, firm size, earnings volatility and GDP are considered as explanatory variables. According to the fixed effect regression analysis, only 22% of the movements in share prices are explained by the explanatory variables considered in this study. Dividend yield shows significant positive impact on share price volatility whereas dividend per share shows the significant negative impact on share price movements. Exchange rate and firm size illustrate significant negative influence on share price volatility by indicating if firm size is large share price volatility will be high. But, dividend pay-out, financial leverage, earnings volatility and GDP are not significantly convince the share price volatility in this study. Therefore, it is concluded that dividend yield, dividend per share, exchange rates and firm size have significant impact on price volatility in Sri Lankan context. Dividend policy can be considered as the protective mechanism to maintain share price volatility in order to enhance the shareholders wealth.